MOLECULAR DOCKING AND DYNAMICS OF BIOACTIVE COMPOUNDS DERIVED FROM Sauropus androgynus AS CYCLOOXYGENASE-2 INHIBITORS - Aisyah, Aisyah; Utami, Wiji; Faadila, Ayu (Walisongo Journal of Chemistry, 2025)
Inflammation is a biological response to injury that can become chronic and lead to various immunological disorders in humans. Bioactive compounds in Sauropus androgynus exhibit a broad spectrum of biological activity, including anti-inflammatory effects. This study employed a computational approach involving Lipinski’s Rule of Five, protein network analysis, molecular docking, ADMET prediction, molecular dynamics simulations, and Density Functional Theory (DFT) calculations for electronic structure elucidation. Among the tested compounds, corchoionoside C and afzelin demonstrated the strongest inhibitory potential against the COX-2 enzyme, with binding energies of −9.57 and −9.14 kcal/mol, respectively. Molecular dynamics simulations showed that the S. androgynus bioactive compound–COX-2 complexes exhibited minimal fluctuation and remained highly stable throughout the simulation, supporting their potential biological activity. DFT HOMO–LUMO analysis further indicated the capability of corchoionoside C and afzelin to interact with biological targets such as COX-2 through polar or electrostatic interactions. These findings are expected to provide a scientific foundation for the development of novel anti-inflammatory agents with promising pharmacological profiles and reduced adverse effects.